2018
DOI: 10.4168/aard.2018.6.s1.s58
|View full text |Cite
|
Sign up to set email alerts
|

Research on pediatric allergic rhinitis in Korea

Abstract: Allergic rhinitis is the most common chronic rhinitis in children and is the most common allergic disease in childhood and adolescence in Korea and most countries around the world. In this review article, we have summarized some of the research articles on allergic rhinitis that have been published in the Korean Academy of Pediatric Allergy and Respiratory Disease (KAPARD) Journals so far in order to celebrate and look back on the 30th anniversary of the KAPARD. Over the past 30 years, the members of the KAPAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…1,2 AR prevalence, defined as having current symptoms with one or more positive results of the skin prick test (SPT), is about 21% 3 and shows a growing trend among children in Korea. 4 Several potential causes of this increase have been hypothesized, but a change in lifestyle, especially dietary habits, is considered an important factor. 2 Several reports state that Western diets including high amounts of fats and processed foods are associated with an increase in AR or allergy symptoms in children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 AR prevalence, defined as having current symptoms with one or more positive results of the skin prick test (SPT), is about 21% 3 and shows a growing trend among children in Korea. 4 Several potential causes of this increase have been hypothesized, but a change in lifestyle, especially dietary habits, is considered an important factor. 2 Several reports state that Western diets including high amounts of fats and processed foods are associated with an increase in AR or allergy symptoms in children.…”
Section: Introductionmentioning
confidence: 99%
“…Allergic rhinitis (AR) is a common disease affecting 10%‐30% of children in developed countries, and its prevalence has slightly increased worldwide 1,2 . AR prevalence, defined as having current symptoms with one or more positive results of the skin prick test (SPT), is about 21% 3 and shows a growing trend among children in Korea 4 . Several potential causes of this increase have been hypothesized, but a change in lifestyle, especially dietary habits, is considered an important factor 2 …”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review of the prevalence rates of allergic diseases in Korea over the past 30 years found continuous increases in the rates of allergic rhinitis, allergic conjunctivitis, atopic dermatitis, and food allergy, although there was no distinct trend in the prevalence of asthma [2]. A notable observation was that the prevalence of allergic rhinitis in children has continuously increased in recent decades [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…These two diseases have commonalities in causing oral and respiratory dryness and have been linked to oral health disorders. In studies using allergic rhinitis as a dependent variable 3,8,9) there are no studies on the relevance of oral health.…”
Section: Introductionmentioning
confidence: 99%